2010
DOI: 10.1246/cl.2010.1086
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Copper-mediated 1,3-Dipolar Cycloaddition of Pyrazolidinone-based Dipoles to Terminal Alkynes to Produce N,N-Bicyclic Pyrazolidinone Derivatives

Abstract: A simple dinuclear copper complex [Cu(®-OH)(tmen)] 2 Cl 2 (tmen = N,N,N¤,N¤-tetramethylethylenediamine) could act as an effective precatalyst for the 1,3-dipolar cycloaddition of pyrazolidinone-based dipoles to terminal alkynes to produce the corresponding N,N-bicyclic pyrazolidinone derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The products were confirmed by the comparison of their NMR spectra with those of authentic data. [7][8][9]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The products were confirmed by the comparison of their NMR spectra with those of authentic data. [7][8][9]…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Fu and co‐workers reported for the first time that the 1,3‐dipolar cycloaddition of azomethine imines to terminal alkynes also proceeds regioselectively in the presence of copper(I) salts and certain nitrogen‐based ligands 7. Although copper‐catalyzed cycloaddition is a powerful method for the synthesis of N , N ‐bicyclic pyrazolidinone derivatives, only a few catalysts have been reported until now; for example, CuI/nitrogen‐based ligands,7 [Cu(μ‐OH)(tmen)] 2 Cl 2 (tmen= N , N , N′ , N′ ‐tetramethylethylenediamine),8 and copper(I)‐exchanged zeolites 9. In addition, these systems have shortcomings such as 1) low turnover frequency (TOF) and turnover number (TON), 2) difficulty in catalyst/product(s) separation and catalyst reuse, and/or 3) indispensability of additives such as stabilizing ligands.…”
Section: 3‐dipolar Cycloaddition Reaction Of 1 a To 2 A With Varioumentioning
confidence: 99%
See 1 more Smart Citation
“…Fu and co-workers reported regioselective and enantioselective copper(I)catalyzed [3+2] coupling of achiral 3-pyrazolidinon-1-azomethine imines with terminal acetylenes to generate optically active pyrazolo[1,2-a]pyrazolone derivatives in 74 -98 % ee [20,21]. Since then, several other examples of catalyzed cycloadditions of 3pyrazolidinone-derived azomethine imines to terminal acetylenes have been published comprising catalysis by CuI [22], di-copper-substituted silicotungstate [23], [Cu(µ-OH)(tmen)] 2 Cl 2 [24], Cu-USY-zeolites [25,26], Cu(OH) x /Al 2 O 3 [27], CuOAc [28], AgN(SiMe 3 ), and CuN(SiMe 3 ) 2 [29]. Moreover, Kobayashi and coworkers also showed that regiochemistry of these reactions can be tuned by the choice of the ligand [29].…”
Section: Introductionmentioning
confidence: 99%
“…Procedures and data for all products 4-7 were in accordance with the literature; [13] Because organoazides are excellent precursors for primary amines, we activated the two primary alcohol functions of compound 6 by sulfonyl ester formation (74 % of product 8, Scheme 3) and converted it by treatment with sodium azide in EtOH by common protocols. Bis-triazole 10 was formed in 81 % yield in the presence, as catalyst, of the commercially available [Cu(μ-OH)(tmeda)] 2 Cl 2 complex, [16] which we had already reported be superior to the standard precatalyst (CuSO 4 , sodium ascorbate). Catalytic hydrogenation of this material proceeded smoothly to give, once again, a unique material (89 % yield) that was mass-spectrometrically and NMRspectroscopically consistent with the constitution of bisaminomethyl compound 1.…”
Section: Resultsmentioning
confidence: 99%